2013
DOI: 10.1002/ps.3605
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐rich culture conditions enhance the conidial infectivity and the quality of two strains of Isaria fumosorosea for potentially improved biocontrol processes

Abstract: An enriched oxygen atmosphere increases the quality of conidia of both strains of I. fumosorosea, with a variable effect on conidium production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
30

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 28 publications
1
12
1
30
Order By: Relevance
“…Similarly in this study, we observed that the conidial hydrophobicity and the virulence of the conidia against T. molitor larvae were not strongly associated. In a recent report by Miranda-Hernández et al (2014), conidia of I. fumosorosea obtained under a modified atmosphere containing 26 % O 2 exhibited high virulence against Galleria melonella larvae (waxworm), and also that these conidia developed a cross protection mechanism against other kinds of stresses, although this phenomenon was not detected in the present study with M. anisopliae var. lepidiotum.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Similarly in this study, we observed that the conidial hydrophobicity and the virulence of the conidia against T. molitor larvae were not strongly associated. In a recent report by Miranda-Hernández et al (2014), conidia of I. fumosorosea obtained under a modified atmosphere containing 26 % O 2 exhibited high virulence against Galleria melonella larvae (waxworm), and also that these conidia developed a cross protection mechanism against other kinds of stresses, although this phenomenon was not detected in the present study with M. anisopliae var. lepidiotum.…”
Section: Discussioncontrasting
confidence: 78%
“…Similarly, when Saccharomyces cerevisiae is exposed to 100 % O 2 (hyperoxia), this microorganism develops a number of stress response factors, including those involved in antioxidant defence, heat shock, DNA and protein damage repair (Outten et al 2005). In a similar way, when the I. fumosorosea conidia were obtained in the presence of an atmosphere containing 26 % O 2 , the catalase activity increased by 50 % (Miranda-Hernández et al 2014), and this same response was reported for Neurospora crassa when the strain was exposed to H 2 O 2 (Aguirre et al 2005;Angelova et al 2005).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For instance, M. anisopliae showed higher conidial production under OEP without affecting germination and infectivity on T. molitor larvae (Tlecuitl-Beristain et al, 2010). Interestingly, when two strains of Isaria fumosorosea were tested, conidia produced with OEP increased the pathogenicity against Galleria mellonella larvae for both strains, although those strains showed a variable effect on conidia production, OEP treatments induced also a cross protection phenotype against osmotic stress in the conidia (Miranda-Hernández et al, 2014). Similarly, in the present study conidial yields were strain dependent when grown under oxidant pulses, although pathogenicity performance of conidia was enhanced in those obtained from OEP-D (t 0 in strain 88 and ST 50 in strain 885.2).…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies on the effect of oxygen concentration on yields and quality of conidia produced by entomopathogenic fungi (EF) have shown that the application of oxygen pulses (O 2 at 26%) improved conidia production for Metarhizium anisopliae (Tlecuitl-Beristain et al, 2010). On the other hand, two strains of Isaria fumosoroseae growing on surface culture showed a variable effect in response to the presence of 26% oxygen in the atmosphere (Miranda-Hernández et al, 2014). B. bassiana grown on rice grains showed a higher production of conidia in batches treated with 16% or 26% oxygen pulses when compared to normal atmospheric conditions at 21% oxygen (Garza-López et al, 2012).…”
Section: Introductionmentioning
confidence: 98%